THE EFFECTS OF INDUCED BLOOD PRESSURE INCREASE AND DECREASE ON CEREBRAL SMALL VESSELS: THE HYPERINTENSE STUDY. (June 2022) - Janssen, Esther; Ter Telgte, Annemieke; Verburgt, Esmée; De Jong, Joost; Marques, José; Kessels, Roy; Backes, Walter; Maas, Marnix; Meijer, Anton; Deinum, Jaap; Riksen, Niels; Tuladhar, Anil; et al.
Abstract : Objective: Cerebral Small vessel disease (SVD) is a disorder of the cerebral microvessels and is the commonest vascular cause of stroke and dementia. Hypertension is the most established risk factor for SVD, but the pathophysiological mechanisms following hypertension that cause SVD remain poorly understood. We aim to examine the effects of changes in blood pressure on cerebral microvasculature in young- and middle-aged adults with hypertension to detect the earliest microvascular changes associated with SVD. Design and method: The Hyperintense study is an ongoing observational cohort study aiming to include 50 hypertensive adults (18–55 years). These patients temporarily discontinue antihypertensive medication for diagnostic purposes, often leading to a temporary increase in blood pressure. Data are collected before medication withdrawal (T = 0), once antihypertensives are withdrawn (T = 1), when patients have restarted medication and reached target blood pressure (T = 2) and 1 year later (T = 3). At each time-point, high-resolution 3T MRI scans are performed with conventional structural sequences and advanced techniques to assess various aspects of microvascular integrity, including integrity of the blood-brain barrier, microperfusion and microstructural integrity. Clinical data includes motor and cognitive examinations and blood sampling. Results: Between July-December 2021, 7 patients (86% male, mean age 47.4 ± 4.4 years) were enrolled. Baseline characteristics and SVD burden are shown in Table. In 3/4 participants who completed T = 1, systolic blood pressure increased after medication withdrawal (median increase systolic blood pressure: 13.7 [3.3 – 15.3] mmHg), demonstrating proof of principle of our approach. Conclusions: First data show increased blood pressure after medication withdrawal in most participants and demonstrate feasibility of our design. Analysis of the effect of blood pressure increase and decrease on MRI outcomes will improve understanding of the pathological mechanisms following hypertension that may lead to MRI markers of SVD. This knowledge can help identify new targets for treatment of SVD, aimed at preventing or limiting disease progression.